Persepsi Follower Terhadap Pemasaran Restoran melalui Instagram di Surabaya - Regina Jokom (Universitas Negeri Surabaya, 2018)
Instagram is one of social media which is growing popular currently. Food photography trend cause restaurants use Instagram as one of their marketing tools. Therefore, this research aims to describe restaurant followers perception toward Instagram marketing communication. The components of marketing communication used are context, communication, collaboration and connection. Furthermore, 791 questionnaires are collected through survey to the followers. The result shows followers perceived that the overall marketing communication is good. Among four components of marketing communication, context is perceived the best in terms of using understandable language and interesting picture or photo. On the other side, the collaboration needs to be improved. Therefore, restaurants need to enhance the content with more interesting and interactive posting instead of only give product or price information. In addition, restaurants should pay more attention to the followers comments and questions with answering and responding to it.